Difficult-to-treat rheumatoid arthritis: contributing factors and burden of disease - Roodenrijs, Nadia M T; van der Goes, Marlies C; Welsing, Paco M J; Tekstra, Janneke; Lafeber, Floris P J G; Jacobs, Johannes W G; van Laar, Jacob M (Rheumatology (Oxford, England), 2021)
Treatment of difficult-to-treat (D2T) RA patients is generally based on trial-and-error and can be challenging due to a myriad of contributing factors. We aimed to identify risk factors at RA onset, contributing factors and the burden of disease. Consecutive RA patients were enrolled and categorised as D2T, according to the EULAR definition, or not (controls). Factors potentially contributing to D2T RA and burden of disease were assessed. Risk factors at RA onset and factors independently associated with D2T RA were identified by logistic regression. D2T RA subgroups were explored by cluster analysis. Fifty-two RA patients were classified as D2T and 100 as non-D2T.Lower socioeconomic status at RA onset was found as an independent risk factor for developing D2T RA (OR 1.97 (95%CI 1.08-3.61)). Several contributing factors were independently associated with D2T RA, occurring more frequently in D2T than non-D2T patients: limited drug options because of adverse events (94% vs 57%) or comorbidities (69% vs 37%), mismatch in patient's and rheumatologist's wish to intensify treatment (37% vs 6%), concomitant fibromyalgia (38% vs 9%) and poorer coping (worse levels). Burden of disease was significantly higher in D2T RA patients. Three subgroups of D2T RA patients were identified: 1) 'non-adherent dissatisfied patients'; 2) patients with 'pain syndromes and obesity'; 3) patients closest to the concept of 'true refractory RA'. This comprehensive study on D2T RA shows multiple contributing factors, a high burden of disease and the heterogeneity of D2T RA. These findings suggest that these factors should be identified in daily practice in order to tailor therapeutic strategies further to the individual patient.